Cultural Transformation through Contextual Mission Approach in the Digital Age - Langi, Elsjani Adelin; Nyaming, Fransiskus Gregorius; Palempung, Franty F.; Freidelien Pantow, Anita Grays; Nendissa, Julio Eleazer; Kowal, Jeniar Rainhard (Studia Philosophica et Theologica, 2025)
Cultural transformation in today's global society brings both challenges and opportunities for the implementation of contextual mission, especially in the digital era. Cultural contexts influenced by globalization and technological advances demand missiological strategies that are able to adapt to the changing dynamics of society. Digitalization creates new spaces for cross-cultural interaction, but also introduces complexities such as changing cultural identities, weakening traditional values, and increasing secularism. This research aims to analyze the main challenges facing contextual missions in the digital age, including the technology gap, the diversity of cultural interpretations, and the need for more inclusive dialogue. It also highlights opportunities such as increased access to communication, the potential of global networks, and the formation of digital communities that support spiritual and social transformation. This research utilizes a qualitative-descriptive approach with a literature study data collection method that contributes to the development of missiology discourse by offering a conceptual framework for contextually relevant missions in the digital age. The research results provide new insights for practitioners and academics in responding to contextual needs through a more creative, inclusive, and technology-based approach. With this transformation of understanding, contextual mission can play a more effective role in building cross-cultural relationships, supporting social change, and creating spiritual significance.